1998
DOI: 10.1074/jbc.273.34.21585
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of Human NTH1, a Homolog ofEscherichia coli Endonuclease III

Abstract: The human endonuclease III (hNTH1), a homolog of the Escherichia coli enzyme (Nth), is a DNA glycosylase with abasic (apurinic/apyrimidinic (AP)) lyase activity and specifically cleaves oxidatively damaged pyrimidines in DNA. Its cDNA was cloned, and the full-length enzyme (304 amino acid residues) was expressed as a glutathione S-transferase fusion polypeptide in E. coli. Purified wild-type protein with two additional amino acid residues and a truncated protein with deletion of 22 residues at the NH 2 terminu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
168
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 230 publications
(175 citation statements)
references
References 38 publications
7
168
0
Order By: Relevance
“…This enzyme specifically cleaves oxidatively damaged pyrimidines in DNA. 45,46 Lack of this activity in cervical cancer could contribute to further genomic instability. Interestingly, 2 of the cancer-related genes in clusters 1A and 7A are regulated in a way which is not consistent with data from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme specifically cleaves oxidatively damaged pyrimidines in DNA. 45,46 Lack of this activity in cervical cancer could contribute to further genomic instability. Interestingly, 2 of the cancer-related genes in clusters 1A and 7A are regulated in a way which is not consistent with data from the literature.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the overexpression of OGG1 and MUTYH suppress mutations by 8-oxo-Gua in cultured cells [30,31]. The NTH1 and NEIL1 proteins are homologues of Escherichia coli Nth and Nei, DNA glycosylases that are specific for oxidized pyrimidine bases [32][33][34][35][36][37][38][39]. The observation that NTH1 can be efficiently trapped to an oligonucleotide duplex containing 8-oxo-Gua:C by treatment with NaBH 4 , suggests that NTH1 binds to 8-oxo-Gua:C DNA [40].…”
Section: Introductionmentioning
confidence: 99%
“…The Ntg1 protein exists primarily in mitochondria, although some is found in the nucleus as well (55). Ntg1 is required for the repair of oxidative DNA damage in vivo, and it shares amino acid sequence similarity with E. coli endonuclease III and the human Nth1 protein (21). Ntg1 has DNA repair glycosylase and apurinic/apyrimidinic (AP) lyase activities.…”
Section: Thementioning
confidence: 99%